2016
DOI: 10.1534/g3.115.025718
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Linkage Map of the Medicinal Mushroom Agaricus subrufescens Reveals Highly Conserved Macrosynteny with the Congeneric Species Agaricus bisporus

Abstract: Comparative linkage mapping can rapidly facilitate the transfer of genetic information from model species to orphan species. This macrosynteny analysis approach has been extensively used in plant species, but few example are available in fungi, and even fewer in mushroom crop species. Among the latter, the Agaricus genus comprises the most cultivable or potentially cultivable species. Agaricus bisporus, the button mushroom, is the model for edible and cultivable mushrooms. We have developed the first genetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…bisporus . This result indicated that the position of PR160 and/or of the ITS locus likely differed between these two species, despite their high level of macro-synteny [ 28 ]. In strain CA487, ITSI is most likely functional because offspring having only the ITSI-a or the ITSI-b alleles are viable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bisporus . This result indicated that the position of PR160 and/or of the ITS locus likely differed between these two species, despite their high level of macro-synteny [ 28 ]. In strain CA487, ITSI is most likely functional because offspring having only the ITSI-a or the ITSI-b alleles are viable.…”
Section: Discussionmentioning
confidence: 99%
“…bisporus homolog was close to MAT and the centromere (PRS088 marker), and its tight linkage with the centromere was recently confirmed in A . subrufescens [ 26 ] and more generally a highly conserved macro-synteny between the two species [ 28 ]. Then, two other A .…”
Section: Methodsmentioning
confidence: 99%
“…Here, we report four high‐quality genome sequences of Hymenochaetales species that are global tree pathogens of particular importance. To date, chromosome‐level assemblies are available only for a few basidiomycetous species (Alfaro et al., ; Foulongne‐Oriol et al., ; Stajich et al., ) including P. noxius (Table ). Orthologous relationships with other complete genomes of basidiomycetes have confirmed conservation of karyotypes with few fusion or breaks in Agaricomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may be relevant to the recombination landscape is that the BSN locus (basidial spore* number), determining the number of nuclei per dispersing spore* and thus the automictic* versus outcrossing behaviors, is linked to the mating‐type locus (Imbernon et al ., 1996). Within the Agaricus genus, the recombination suppression around the mating‐type locus also has been reported in the distant species A. subrufescens (Thongklang et al ., 2014; Foulongne‐Oriol et al ., 2016) and A. sinodeliciousus (Ling et al ., 2019). In A. subrufescens , a genetic linkage map suggested a normal recombination behavior on the rest of the genome (Foulongne‐Oriol et al ., 2016).…”
Section: Further Recombination Suppression Beyond Fungal Mating‐type mentioning
confidence: 99%